2012
DOI: 10.1111/j.1365-2591.2012.02106.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of proanthocyanidins on the bond strength and durability of resin sealer to root dentine

Abstract: Treating root dentine with PAs-rich grape seed extracts improved the biodegradation resistance of demineralized root dentine and enhanced the bond strength and durability between resin-based sealer and root dentine after short-term water storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
4
29
1
3
Order By: Relevance
“…In our pilot study, 5 min EDTA irrigation is suitable to see clearly intact porous collagen in the middle third of root canal. In addition, another study reported the use of 10 min PA (Proanthocyanidins, a group of polyphenol found in grape seed) irrigation to enhance the bond strength and durability between resinbased sealer and root dentin 31) . To best of our knowledge, this is the first study to use EGCG as an endodontic final irrigant in order to stabilize the collagen and improve the bond strength of an epoxy resin sealer.…”
Section: Discussionmentioning
confidence: 99%
“…In our pilot study, 5 min EDTA irrigation is suitable to see clearly intact porous collagen in the middle third of root canal. In addition, another study reported the use of 10 min PA (Proanthocyanidins, a group of polyphenol found in grape seed) irrigation to enhance the bond strength and durability between resinbased sealer and root dentin 31) . To best of our knowledge, this is the first study to use EGCG as an endodontic final irrigant in order to stabilize the collagen and improve the bond strength of an epoxy resin sealer.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the structural integrity of the hybrid layer against hydrolytic and enzymatic degradation is of prime importance and is an important issue for providing long-term clinical success. 5 Dentin adhesion creates a resin-enveloped collagen scaffold that, ideally will remain in place for decades. 10 Nevertheless, the hybrid layer may be degraded over time, leading to failure of the adhesive interface.…”
Section: Discussionmentioning
confidence: 99%
“…This agent consequently increases the mechanical properties of root canal dentin collagen, enhances biodegradation resistance and improves bond durability. 5 An electrical glass fiber post system, ever Stick post (GC, India), is available in an uncured flexible form and hence can be adapted to take up the morphological shape of the root canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proanthocyanidin consists of a free hydroxyl phenyl group that has the ability to bind a protein amino acid. The phenyl hydroxyl group forms [10,[17][18][19]. Therefore, in this study, the application of GSE solution for 30 seconds was sufficient for increasing the cross-linking of collagen dentin, according to research by Liu and Wang [9].…”
Section: Discussionmentioning
confidence: 99%